2016
DOI: 10.1073/pnas.1601091113
|View full text |Cite
|
Sign up to set email alerts
|

The neural chaperone proSAAS blocks α-synuclein fibrillation and neurotoxicity

Abstract: Emerging evidence strongly suggests that chaperone proteins are cytoprotective in neurodegenerative proteinopathies involving protein aggregation; for example, in the accumulation of aggregated α-synuclein into the Lewy bodies present in Parkinson’s disease. Of the various chaperones known to be associated with neurodegenerative disease, the small secretory chaperone known as proSAAS (named after four residues in the amino terminal region) has many attractive properties. We show here that proSAAS, widely expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 75 publications
(81 reference statements)
3
74
0
Order By: Relevance
“…Figure 7A, bottom row depicts a representative Neuro2A cell. The fact that expression of excess cyto-proSAAS can efficiently block the cytosolic aggregation of Cherry-cyto-proSAAS supports the general anti-aggregant functions of proSAAS previously documented for Abeta 1-42, α-synuclein, and islet amyloid polypeptide (Hoshino et al, 2014;Jarvela et al, 2016;Peinado et al, 2013).…”
Section: Cherry-cyto-prosaas Forms Spheres Only In the Presence Of Exsupporting
confidence: 79%
See 4 more Smart Citations
“…Figure 7A, bottom row depicts a representative Neuro2A cell. The fact that expression of excess cyto-proSAAS can efficiently block the cytosolic aggregation of Cherry-cyto-proSAAS supports the general anti-aggregant functions of proSAAS previously documented for Abeta 1-42, α-synuclein, and islet amyloid polypeptide (Hoshino et al, 2014;Jarvela et al, 2016;Peinado et al, 2013).…”
Section: Cherry-cyto-prosaas Forms Spheres Only In the Presence Of Exsupporting
confidence: 79%
“…Prior work has shown that proSAAS, a small unglycosylated protein chaperone which contains no α-crystallin domain, is able to block and/or prevent the aggregation of proteins directly involved in neurodegenerative disorders, including Abeta and α-Syn (Hoshino et al, 2014;Jarvela et al, 2016). ProSAAS, found specifically in tissues such as neurons and endocrine cells which contain a regulated secretory pathway, has been found to be associated with plaques, Lewy bodies, and other brain aggregates in AD, PD and FTLD (Jarvela et al, 2016;Kikuchi et al, 2003). However, whether proSAAS directly affects the formation of intracellular aggregates has not been examined in living cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations